A Study on the Correlation Between Media Usage Frequency and Audiences’ Risk Perception, Emotion and Behavior - Li, Peng-Peng; Zhong, Fangqi (Frontiers in Psychology, 2022)
Whether risk events can be effectively controlled and mitigated is largely influenced by people's perceptions of risk events and their behavioral cooperation. Therefore, this study used a web-based questionnaire (N=306) to investigate the specific factors influencing people's risk perceptions and behaviors, and included a test for the difference in the effect of positive and negative emotions of the audiences. The results show that the overall model has good explanatory power (R²= 61%) for the behavioral variables, and (1) how people's use of different media (especially TV and online media) significantly influenced their positive and negative emotions; (2) how people's frequency of TV use significantly influenced their risk susceptibility and how online media use significantly influenced their risk severity (with some differences in people's perceptions of efficacy between different media); (3) how people's sense of efficacy for risky events is the strongest predictor of their risk control behavior; and (4) that there are different mediating effects of different emotions and risk severity and sense of efficacy between the frequency of media use and risk control behavior.